Poor adherence and low persistency rates for hepatocellular carcinoma surveillance in patients with chronic hepatitis B. Issue 35 (August 2016) - Wang, Christina; Chen, Vincent; Vu, Vinh; Le, An; Nguyen, Linda; Zhao, Changqing; Wong, Carrie R.; Nguyen, Nghia; Li, Jiayi; Zhang, Jian; Trinh, Huy; Nguyen, Mindie H.
Abstract : Abstract: Our goal was to examine rates and predictors for hepatocellular carcinoma (HCC) surveillance adherence and persistency, since studies of such adherence and persistency in patients with chronic hepatitis (CHB) are currently limited. Consecutive CHB patients (N = 1329) monitored for ≥1 year at 4 US clinics from January 1996 to July 2013 were retrospectively studied. Surveillance adherence was evaluated based on the American Association for the Study of Liver Diseases guidelines. Kaplan–Meier method was used to analyze surveillance persistency of 510 patients who had initially fair adherence (having at least annual surveillance imaging with further follow-up). Mean age was 48, with the majority being male (58%), Asian (92%), foreign-born (95%), and medically insured (97%). Patients with cirrhosis and those seen at university liver clinics were more likely to have optimal HCC surveillance than those without cirrhosis and those seen at community clinics (38.4% vs 21.6%, P <0.001 and 33.5% vs 14.4%, P < 0.001, respectively). HCC diagnosed in optimally adherent patients trended toward smaller tumor size ( P < 0.08). On multivariate analysis also inclusive of age, sex, clinical visits, cirrhosis, clinic setting and antiviral therapy use, strong independent predictors for having at least annual imaging were a history of more frequent clinical visits (odds ratio [OR] = 2.5, P < 0.001) and university-based care (OR = 5.2, P < 0.001). Even for those with initially fair adherence, persistency dropped to 70% at 5 years. Adherence and persistency to HCC surveillance in CHB patients is generally poor. More frequent clinic visits and university-based settings were significant and strong predictors of at least annual HCC surveillance adherence.